2004
DOI: 10.1136/emj.2003.012575
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of interventions to reduce times to thrombolysis

Abstract: Objectives: To estimate the lifesaving potential of interventions to accelerate the administration of intravenous thrombolysis for myocardial infarction. Methods: Data were analysed from a prospective, observational study of all patients transported to hospital by ambulance, who subsequently received intravenous thrombolysis at 20 hospitals and two ambulance services in Victoria, Australia (n = 1147). Regression models estimated the association between predictor variables age, sex, route of referral, symptom o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Previous studies have looked at various methods of reducing DTN, such as emergency department thrombolysis, 4 pre-alert calls for confirmed AMIs, 6 and pre-hospital thrombolysis. These have shown reductions in DTN times of between 21% and 51%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have looked at various methods of reducing DTN, such as emergency department thrombolysis, 4 pre-alert calls for confirmed AMIs, 6 and pre-hospital thrombolysis. These have shown reductions in DTN times of between 21% and 51%.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2] Other work has shown that paramedic electrocardiogram (ECG) interpretation and fast tracking of patients with myocardial infarction to a coronary care unit (CCU) reduces door to needle (DTN) times, [3][4][5] as does thrombolysis in the emergency department. 6 Currently our institution has a target of 30 minutes for DTN 7 in 75% of cases and that an ECG should be carried out within 10 minutes of arrival.…”
mentioning
confidence: 99%
“…In the present study, 28.1% of the patients got to the hospital by ambulance, but the total time taken to start the therapy was not reduced (P=0.81). Studies have shown a reduction in mortality after thrombolytic therapy in patients that received pre-hospital care (8% versus 13%) (P = 0.04) (9)(10) .…”
Section: Discussionmentioning
confidence: 99%
“…11 Once AMI patients decide to access medical care, a substantial number of them do not call EMS, even though the use of EMS and subsequent hospital prenotification have been shown to reduce time delay to reperfusion. [12][13][14] Once the patient has accessed the EMS system, it is important that EMS providers perform an appropriate history and physical examination to evaluate for acute coronary syndromes. EMS providers are often taught that the chief complaint for a patient having an AMI is chest pain.…”
Section: Early Identification Of the Stemi Patientmentioning
confidence: 99%